Le concept de PES pour une gestion durable des eaux et des sols: application au developpement de l'elevage et au controle environnemental dans le Nord Vietnam - Orange, Didier; Bardouin, L.; Nguyen, D. P.; Loiseau, J.B.; Clement, Floriane; Jouquet, Pascal (2007)
In Northern Vietnam, the urgent environmental problems are soil erosion under annual crop on sloping lands leading to a drastic soil fertility decrease, inducing the risk to unfertilize the flatlands and to fill up the water reservoirs in the downstream part by sediment accumulation. Then a lack of disposable income for the purchase of inorganic fertilizers has resulted in farmers in Northern Vietnam resorting to the utilization of raw animal and human waste in order to fertilizer their cropping systems. This project is dealing at the District level in the Northward of Hoa Binh Province with the PES use (agro-ecological concept of Payment for Environmental Services) based on a new market opportunity for the farmers of Northern Vietnam to mobilise the integrated cattle husbandry enhancement and water management between uplands and lowlands. The purpose is to create a sustainable loop between fodder cropping on sloping lands, the cattle development under stables, the animal and human waste management, leading to human health and water quality protections, to the erosion sediment control for both a sustainable upland and lowland use. The proposed project offers a novel approach in that a holistic approach is introduced to achieve income generation from livestock manure management in mountainous environment of Southeast Asia in establishing a process of comprehensive assessment, of mutual learning between farmers from upper part and down part of the watershed through a hydrological modelling platform, and by the development of new agricultural technologies as biogas digester and vermicompost unit.